2018
DOI: 10.1017/s1751731117003603
|View full text |Cite|
|
Sign up to set email alerts
|

Quality of eggs from Lohmann Brown Classic laying hens fed black soldier fly meal as substitute for soya bean

Abstract: Soya bean is the main protein source in poultry feed but rising prices make an alternative protein source necessary. Insects, such as the black soldier fly (Hermetia illucens), may be an attractive solution for hens, although little information is available on their effect on egg quality. The present study aims to fill this gap by testing the effect of 100% replacement of soya bean with H. illucens larva meal in the diet of Lohmann Brown Classic laying hens for 21 weeks. At the end of the trial, the eggs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
80
2
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(106 citation statements)
references
References 24 publications
18
80
2
3
Order By: Relevance
“…Moreover, it was observed that a reduction in the amount of corn led to lower values of redness and yellowness. In the same line, Secci et al [11] also obtained variations in the redness values, when comparing a soy-based diet with another diet based on insects in Lohman Brown hens; meanwhile, parameters L* and b* were not affected. However, Kostogrys et al [33] did not find changes in a*, but they found L* and b* varied, when pomegranate seed oil was incorporated into the diet of Isa Brown hens.…”
Section: Effect Of Breed and Diet Type On Egg Color Parametersmentioning
confidence: 76%
See 2 more Smart Citations
“…Moreover, it was observed that a reduction in the amount of corn led to lower values of redness and yellowness. In the same line, Secci et al [11] also obtained variations in the redness values, when comparing a soy-based diet with another diet based on insects in Lohman Brown hens; meanwhile, parameters L* and b* were not affected. However, Kostogrys et al [33] did not find changes in a*, but they found L* and b* varied, when pomegranate seed oil was incorporated into the diet of Isa Brown hens.…”
Section: Effect Of Breed and Diet Type On Egg Color Parametersmentioning
confidence: 76%
“…The fat content in eggs can be increased, modifying the final diet [40], by increasing the cashew amount in the diet. In contrast, Secci et al [11] did not obtain significant changes in the eggs' composition when they compared a soy-based diet to an insect-based diet. In another study, where standard commercial feeding was compared with a fodder enriched in pomegranate seed oil, the group of hens fed with pomegranate seed oil obtained lower values for protein percentage, but the ash and moisture contents were higher in comparison with those of the control group's [33].…”
Section: Effect Of Breed and Diet Type On Egg Textural Parameters Andmentioning
confidence: 87%
See 1 more Smart Citation
“…Insects have been proposed as a high quality, efficient, and sustainable alternative protein source (De Marco et al 2015;Marono et al 2017;Dabbou et al 2018;Mwaniki et al 2018;Secci et al 2018). Using insects as a protein source can contribute to global food security via feed or as a direct food source for humans (Schader et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Insect meal is included as a substitute for soya and fish meal in feed for fish and poultry and is envisaged also for farm animals such as pigs and cattle. The use of insects in dog and cat food is a developing market especially in the USA.…”
Section: Allergies To Ingested Insectsmentioning
confidence: 99%